Preparation of nano composite permanent magnet material with high magnetic energy product and strong coercive force

By using MnBi alloy and Fe-Ni alloy to prepare nanocomposite permanent magnet materials, nanoscale composite of hard magnetic phase and soft magnetic phase is achieved, the problem of insufficient resource consumption and performance of rare earth permanent magnet materials is solved, and high magnetic energy product and Materials with strong coercivity have expanded their application prospects.

CN119480412AActive Publication Date: 2025-02-18HEYE HEALTH TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411643680.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The excessive resource consumption and price increase of rare earth permanent magnet materials limit their application, and existing nanocomposite permanent magnet materials have shortcomings in magnetic properties and coercivity.

Method used

Using MnBi alloy and Fe-Ni alloy as raw materials, the preparation of solid epoxy resin, the preparation of hard magnetic phase of Mn55Bi45 alloy, the preparation of nanocrystalline Fe-Ni soft magnetic composite materials, and the preparation of Mn55Bi45/Fe-Ni nanocomposite permanent magnet materials Preparation to realize nanoscale recombination of hard magnetic phase and soft magnetic phase.

Benefits of technology

Nanocomposite permanent magnet materials with high magnetic energy product and strong coercive force were obtained, which alleviated the problem of excessive consumption of rare earth resources and expanded the application prospects of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480412A_ABST
    Figure CN119480412A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a nano composite permanent magnet material with high magnetic energy product and strong coercive force, which comprises the following steps of: preparing solid epoxy resin, preparing a MnBi alloy cast ingot, preparing a Mn55Bi45 alloy hard magnetic phase bonded magnet, preparing a nanocrystalline Fe-Ni soft magnetic composite material, and preparing a Mn55Bi45 / Fe-Ni nano composite permanent magnet material. According to the invention, an electric arc melting method, a mechanical alloying method, a high-energy ball milling method, a heat treatment process and other methods are creatively combined, and the prepared nano composite permanent magnet material has the characteristics of high magnetic energy product, excellent coercive force, high saturation magnetization, acid and alkali resistance, high performance, low cost and the like; therefore, the Mn55Bi45 / Fe-Ni nano composite permanent magnet material has remarkable advantages in medical equipment application occasions of the large health industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a nano composite permanent magnetic material with high magnetic energy product and strong coercive force, belonging to the technical field of new materials. Background Art

[0002] With the continuous development of human society, rare earth permanent magnet materials play an indispensable role in strategic emerging industries such as new energy vehicles, wind power generation, and robots. However, the excessive consumption of rare earth resources and the sharp rise in prices have limited the application of rare earth permanent magnet materials. In order to cope with the limitations of rare earth permanent magnet materials, the present invention uses MnBi alloy as a raw material. MnBi alloy is a new type of rare earth-free high-performance permanent magnet material with the advantages of high coercivity, moderate saturation magnetization intensity and magnetic energy product, and Mn 55 Bi 45 As a ratio of MnBi alloy, it has excellent magnetic properties, while Fe-Ni alloy, as one of the raw materials, is a typical soft magnetic material, and also has the characteristics of high saturation magnetization and low coercivity. It also has a positive coercivity temperature coefficient within a certain range, making it a potential permanent magnet material for medium and high temperature applications.

[0003] In the field of nanocomposite permanent magnetic materials, the high saturation magnetization of the soft magnetic phase can be combined with the high magnetocrystalline anisotropy of the hard magnetic phase to obtain excellent magnetic properties through ferromagnetic exchange coupling between the two-phase grains at the nanoscale. Summary of the invention

[0004] In view of the above problems, the present invention provides a method for preparing a nano-composite permanent magnetic material with high magnetic energy product and strong coercive force.

[0005] The present invention relates to a method for preparing a nano-composite permanent magnetic material with high magnetic energy product and strong coercive force, comprising the following steps: step (1) preparing a solid epoxy resin, step (2) preparing a MnBi alloy ingot, step (3) preparing a Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets, step (4) Preparation of nanocrystalline Fe-Ni soft magnetic composite materials, step (5) Mn 55 Bi 45 / Preparation of Fe-Ni nanocomposite permanent magnetic materials; Wherein, the preparation of the nanocrystalline Fe-Ni soft magnetic composite material in step (4) comprises: Fe powder and Ni powder are weighed according to a certain metering ratio, and high-energy ball milling is performed. During the process, alcohol is added to prevent the powder from being oxidized. The ball milling atmosphere is argon. Subsequently, epoxy resin is weighed and dissolved in an acetone solution, mixed and stirred, and the above powders are added to the solution, mixed and stirred evenly until completely evaporated; then transferred to a mold, compacted and formed under a certain pressure; finally, annealed at a high temperature for a period of time to obtain a nanocrystalline Fe-Ni soft magnetic composite material; Step (5) Mn 55 Bi 45 / The preparation of Fe-Ni nanocomposite permanent magnetic materials includes: The Mn prepared in step (3) was added to the inert gas glove box chamber with a certain oxygen content. 55 Bi 45 The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (4), and then ball milling is performed. After the ball milling is completed, the powder is collected; after the ball milling powder is collected, a certain amount of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming. When the vacuum degree is lower than a certain amount, the tube sealing work is completed; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to complete the process, and finally Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

[0006] The Mn prepared by the present invention 55 Bi 45 / Fe-Ni nanocomposite permanent magnet material has significant research value and application prospects in today's environment. It combines Mn 55 Bi 45 The advantages of high coercivity and high saturation magnetization intensity of Fe-Ni have excellent magnetic properties, which not only helps to alleviate the problem of excessive consumption of rare earth resources, but also has broad application prospects.

[0007] Preferably, step (1) preparation of solid epoxy resin Add E51 resin and E20 resin into a four-necked flask, then raise the temperature, adjust the stirring rate, and under this condition, dropwise add the chain extender polyaspartic acid ester resin, control the dropping time, and then carry out heat preservation reaction to obtain the chain-extended epoxy resin, then add 1,4-cyclohexanedimethanol diglycidyl ether, and then add a mixed solvent (xylene: n-butanol), adjust the solid content, and obtain a solid epoxy resin; Step (2) Preparation of MnBi alloy ingot The high-purity manganese metal raw material and bismuth metal raw material are ground and then broken into suitable sizes, and a certain amount of raw materials are weighed respectively, and the raw materials are placed in a copper crucible of an arc melting furnace, and then the cavity of the arc melting furnace is evacuated, and then argon gas is injected to ensure that the melting environment is in an oxygen-free environment, and then repeated melting is performed to obtain a block ingot with uniform composition; Step (3) Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets The MnBi alloy ingot obtained in the above step (2) is placed in a tubular vacuum annealing furnace for annealing, and a certain annealing temperature and time are set. When taken out, it is water-cooled to room temperature, and the ingot is taken out for oxide scale grinding, crushed and ground in a glove box to obtain coarse powder, sieved, and the powder is placed in a ball mill, and the ball-to-material ratio is set, and oleic acid is added as a surfactant and ethanol is used as a solvent. Then, the powder is placed in a ball mill and a certain ball milling time is set. After the ball milling is completed, the slurry is washed with anhydrous ethanol and then mixed with paraffin to prepare anisotropic Mn 55 Bi 45 Mn alloy magnetic powder, add acetone to the epoxy resin obtained in step (1), add it to the magnetic powder after it is completely melted, and stir it with a stirrer. As the stirring proceeds, the acetone gradually evaporates, and the epoxy resin and the magnetic powder are evenly mixed together. The magnetic powder mixed with the epoxy resin is molded and then cured at a certain temperature to obtain Mn alloy magnetic powder. 55 Bi 45 Alloy hard magnetic phase bonded magnet; Step (4) Preparation of nanocrystalline Fe-Ni soft magnetic composite material Fe powder and Ni powder are weighed according to a certain metering ratio, added into a stainless steel ball mill, and high-energy ball milling is performed using a planetary high-energy ball mill. During the process, alcohol is added to prevent oxidation of the powder. The ball milling atmosphere is argon gas. The ball milling speed is fixed and the ball milling time is set. Subsequently, epoxy resin is weighed and dissolved in an acetone solution, mixed and stirred for a certain period of time, and the above powders are added into the solution, mixed and stirred evenly until completely evaporated; then the powders are transferred into a ring mold and compacted under a certain pressure; finally, the nanocrystalline Fe-Ni soft magnetic composite material is obtained by annealing at high temperature for a period of time. Step (5) Mn 55 Bi 45 Preparation of Fe-Ni nanocomposite permanent magnetic materials The Mn prepared in step (3) was added to the inert gas glove box chamber with a certain oxygen content. 55 Bi 45The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (4), and then placed in a high-energy ball mill equipped with steel balls, and then the ball mill cover is tightened and taken out from the inert gas glove box. At this time, the ball mill already contains a certain amount of Ar gas, which can protect the powder material from oxidation during the subsequent grinding process; the tightened ball mill is taken out from the inert gas glove box and fixed in a high-energy ball mill, and ball milling is performed according to the experimental set conditions. After the ball milling is completed, the powder is collected in the inert gas glove box; after collecting the ball milled powder, a certain amount of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming, and the tube sealing work is completed when the vacuum degree is lower than a certain amount; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to obtain Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

[0008] Preferably, step (1) preparation of solid epoxy resin Add E51 resin and E20 resin into a four-necked flask, then raise the temperature to 70-80°C, then adjust the stirring rate to 300-400r / min, and under this condition, add the chain extender polyaspartic acid ester resin dropwise, the addition ratio is 4:1-12:3, the addition time is controlled between 2h-3h, and then keep the temperature for 2-3h to react, thereby obtaining the chain-extended epoxy resin, then add 1,4-cyclohexanedimethanol diglycidyl ether, and then add a mixed solvent (xylene: n-butanol = 3:1-5:2), adjust the solid content to 85-90%, and obtain a solid epoxy resin.

[0009] The present invention has the advantage that the solid epoxy resin prepared in this step combines two traditional resins and is modified by adding a chain extender, thereby improving the shortcomings of low-molecular epoxy resins, and the addition of 1,4-cyclohexanedimethanol diglycidyl ether reduces the viscosity of the system, so that the obtained solid epoxy resin has the advantage of high toughness, providing excellent performance for the subsequent preparation steps of composite magnetic materials, and the application prospects of solid epoxy resins are also very broad.

[0010] Preferably, step (2) preparation of MnBi alloy ingot The high-purity manganese metal raw materials and bismuth metal raw materials were ground and then crushed to a suitable size. The raw materials were weighed according to the nominal composition of Mn:Bi=55:45-60:50, and the raw materials were placed in the copper crucible of the arc melting furnace. The cavity of the arc melting furnace was evacuated to a vacuum degree of (3-3.5)×10 -3 Pa, then inject argon gas to - (0.05-0.07) Pa to ensure that the smelting environment is in an oxygen-free environment, and then repeat the smelting 6-7 times to obtain a block ingot with uniform composition; The advantages of the present invention are that, in this step, MnBi alloy is selected as raw material, and MnBi alloy is a new type of non-rare earth permanent magnet material with high coercivity; and arc melting method is used in the step, and the melting speed of this method is relatively fast, and a large amount of metal materials can be melted in a short time, which improves the efficiency of preparing MnBi alloy ingots, reduces production costs and shortens production cycles, and helps to obtain MnBi alloys with uniform composition, and alloys with good uniformity of composition have better magnetic properties and mechanical properties, thereby improving the overall performance of the MnBi alloy ingots, paving the way for subsequent steps.

[0011] Preferably, in step (3), Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets The MnBi alloy ingot obtained in the above step (2) is placed in a tubular vacuum annealing furnace for annealing at an annealing temperature of 563-570K for an annealing time of 24-26 hours. When taken out, the ingot is cooled to room temperature with water. The ingot is taken out for oxide scale polishing, crushed and ground in a glove box to obtain a coarse powder, and sieved with 100-150 mesh. 2-4g of the powder is placed in a ball mill with a ball-to-material ratio of 12.5:1-25:2, and 3-3.5% of oleic acid by weight of the powder is added as a surfactant, 60-80mL of ethanol is used as a solvent, and then the ingot is placed in a ball mill for a ball milling time of 0.5-6 hours. After the ball milling is completed, the slurry is washed with anhydrous ethanol and then mixed with paraffin to prepare anisotropic Mn 55 Bi 45 alloy magnetic powder, add acetone to the epoxy resin obtained in step (1), add it to the magnetic powder after it is completely melted, and stir it with a stirrer. As the stirring proceeds, the acetone gradually evaporates, and the epoxy resin and the magnetic powder are evenly mixed together. The magnetic powder mixed with the epoxy resin is molded and then cured at 120-140°C for 2-3h to obtain Mn 55 Bi 45 Alloy hard magnetic phase bonded magnet; The present invention has the advantage that high-energy ball milling and annealing are used in this step. High-energy ball milling can make Mn 55 Bi 45 The alloy achieves the best magnetic properties in the shortest time, so that it has excellent coercivity performance, which improves the efficiency of the present invention, and the annealing treatment can effectively increase the Mn 55 Bi 45 The alloy's saturation magnetization intensity gives it excellent magnetic properties and provides an excellent performance foundation for the subsequent preparation of composite permanent magnetic materials.

[0012] Preferably, step (4) preparation of nanocrystalline Fe-Ni soft magnetic composite material Fe powder and Ni powder are weighed according to a metering ratio of 100:5-200:10, added into a stainless steel ball mill, and high-energy ball milling is performed using a planetary high-energy ball mill, during which 3-4% alcohol is added to prevent oxidation of the powder, the ball milling atmosphere is argon, the fixed ball milling speed is 300-350r / min, and the ball milling time is 20-50h. Subsequently, 2-3% of epoxy resin by mass is weighed and dissolved in an acetone solution, mixed and stirred for 30-45min, and the above powder is added into the solution, mixed and stirred evenly until completely evaporated; then transferred into a ring mold, compacted and molded at a pressure of 400-450MPa; finally, annealed at a temperature of 550-700℃ for 3-4h to obtain a nanocrystalline Fe-Ni soft magnetic composite material; The advantage of adopting the present invention is that this step adopts a planetary high-energy ball milling method. This complex motion trajectory greatly enhances the impact force and grinding effect of the grinding medium on the material, so that the raw materials can be efficiently refined to the nanometer level. In addition, the high-intensity mechanical force can also ensure the full mixing of different component raw materials. In the preparation of Fe-Ni soft magnetic composite materials, this efficient refinement and mixing can make Fe and Ni elements evenly distributed on the nanometer scale, thereby optimizing the magnetic properties of the material, so that the Fe-Ni soft magnetic composite material finally has the advantages of high magnetic energy product and good coercive force.

[0013] Preferably, in step (5), Mn 55 Bi 45 Preparation of Fe-Ni nanocomposite permanent magnetic materials The Mn prepared in step (3) was added to an inert gas glove box chamber with an oxygen content controlled at 6-8 ppm. 55 Bi 45 The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (4), and then placed in a high-energy ball mill equipped with steel balls. The ball mill cover is then tightened and taken out from the inert gas glove box. At this time, the ball mill contains Ar gas, which can protect the powder material from oxidation during the subsequent grinding process. The tightened ball mill is taken out from the inert gas glove box and fixed in a high-energy ball mill. Ball milling is performed according to the experimental conditions. After the ball milling is completed, the powder is collected in the inert gas glove box. After collecting the ball milled powder, about 0.4-0.5g of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming. When the vacuum degree is lower than (2-3)×10 -4 Pa, the tube sealing work is completed; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to complete the Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

[0014] The present invention has the advantage that the present invention can realize Mn 55 Bi 45 The uniform composite of Fe-Ni at the nanoscale, and Mn 55 Bi 45 As a hard magnetic phase, Fe-Ni as a soft magnetic phase, the composite of the two at the nanoscale can produce a strong exchange coupling effect, which helps to improve the coercivity and magnetic energy product of the composite material, thereby improving its permanent magnetic properties, which makes the final Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic material combines the advantages of both, achieving the advantages of high magnetic energy product and strong coercive force. These advantages make the material have broad application prospects and important research value in the field of permanent magnetic materials.

[0015] In summary, the present invention has the following beneficial effects: 1. The present invention has the advantages that the solid epoxy resin prepared in this step combines two traditional resins and is modified by adding a chain extender, thereby improving the shortcomings of low molecular weight epoxy resins, and the addition of 1,4-cyclohexanedimethanol diglycidyl ether reduces the viscosity of the system, so that the obtained solid epoxy resin has the advantage of high toughness, providing excellent performance for the subsequent preparation steps of composite magnetic materials, and the application prospects of solid epoxy resins are also very broad; 2. The present invention has the advantages that, in this step, MnBi alloy is selected as raw material, and MnBi alloy is a new type of non-rare earth permanent magnet material with high coercivity; and arc melting method is used in the step, and the melting speed of this method is relatively fast, and a large amount of metal materials can be melted in a short time, which improves the efficiency of preparing MnBi alloy ingots, reduces production costs and shortens production cycles, and helps to obtain MnBi alloys with uniform composition, and alloys with good uniformity of composition have better magnetic properties and mechanical properties, thereby improving the overall performance of MnBi alloy ingots, paving the way for subsequent steps; 3. The advantage of the present invention is that high-energy ball milling and annealing are used in this step. High-energy ball milling can make Mn 55 Bi 45 The alloy achieves the best magnetic properties in the shortest time, so that it has excellent coercivity performance, which improves the efficiency of the present invention, and the annealing treatment can effectively increase the Mn 55 Bi 45 The alloy's saturation magnetization intensity gives it excellent magnetic properties and provides an excellent performance foundation for the subsequent preparation of composite permanent magnetic materials; 4. The present invention has the advantage that this step adopts a planetary high-energy ball milling method. This complex motion trajectory greatly enhances the impact force and grinding effect of the grinding medium on the material, so that the raw materials can be efficiently refined to the nanometer level. In addition, the high-intensity mechanical force can also ensure the full mixing of different component raw materials. In the preparation of Fe-Ni soft magnetic composite materials, this efficient refinement and mixing can make Fe and Ni elements evenly distributed on the nanometer scale, thereby optimizing the magnetic properties of the material, so that the Fe-Ni soft magnetic composite material finally has the advantages of high magnetic energy product and good coercive force; 5. The advantage of the present invention is that the present invention can achieve Mn 55 Bi 45 The uniform composite of Fe-Ni at the nanoscale, and Mn 55 Bi 45 As a hard magnetic phase, Fe-Ni as a soft magnetic phase, the composite of the two at the nanoscale can produce a strong exchange coupling effect, which helps to improve the coercivity and magnetic energy product of the composite material, thereby improving its permanent magnetic properties, which makes the final Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic material combines the advantages of both, achieving the advantages of high magnetic energy product and strong coercive force. These advantages make the material have broad application prospects and important research value in the field of permanent magnetic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The present invention is a preparation flow chart of a nano composite permanent magnetic material with high magnetic energy product and strong coercive force. DETAILED DESCRIPTION

[0017] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0018] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products.

[0019] Example 1

[0020] Step (1) Preparation of solid epoxy resin Add E51 resin and E20 resin into a four-necked flask, then raise the temperature to 70°C, adjust the stirring rate to 300r / min, and under this condition, dropwise add chain extender polyaspartic acid ester resin at a dropping ratio of 4:1, and control the dropping time to 2h. Keep the temperature for reaction for 2h to obtain chain-extended epoxy resin, then add 1,4-cyclohexanedimethanol diglycidyl ether, and then add a mixed solvent (xylene: n-butanol = 3:1), adjust the solid content to 85%, and obtain solid epoxy resin; Step (2) Preparation of MnBi alloy ingot The high-purity manganese metal raw materials and bismuth metal raw materials were ground and then crushed to a suitable size. The raw materials were weighed according to the nominal composition of Mn:Bi=55:45, and the raw materials were placed in the copper crucible of the arc melting furnace. The cavity of the arc melting furnace was then evacuated to a vacuum degree of 3×10 -3 After the melting temperature reaches 0.05 Pa, argon gas is injected to -0.05 Pa to ensure that the melting environment is in an oxygen-free environment. Then the melting is repeated 6 times to obtain a block ingot with uniform composition. Step (3) Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets The MnBi alloy ingot obtained in the above step (2) was placed in a tubular vacuum annealing furnace for annealing at an annealing temperature of 563K for 24 hours. When taken out, it was cooled to room temperature with water. The ingot was taken out for oxide scale polishing, crushed and ground in a glove box to obtain coarse powder, and sieved with 100 mesh. The powder was placed in a ball mill with a ball-to-material ratio of 12.5:1, and 3% oleic acid as a surfactant and 60 mL ethanol as a solvent were added. The ingot was then placed in a ball mill and the ball milling time was set for 2 hours. After the ball milling was completed, the slurry was washed with anhydrous ethanol and then mixed with paraffin to prepare anisotropic Mn 55 Bi 45 alloy magnetic powder, add acetone to the epoxy resin obtained in step (1), add it to the magnetic powder after it is completely melted, and stir it with a stirrer. As the stirring proceeds, the acetone gradually evaporates, and the epoxy resin and the magnetic powder are evenly mixed together. The magnetic powder mixed with the epoxy resin is molded and then cured at 120°C for 2h to obtain Mn 55 Bi 45 Alloy hard magnetic phase bonded magnet; Step (4) Preparation of nanocrystalline Fe-Ni soft magnetic composite material Fe powder and Ni powder were weighed according to a metering ratio of 100:5, added into a stainless steel ball mill, and high-energy ball milling was performed using a planetary high-energy ball mill. During the process, 3% alcohol was added to prevent powder oxidation. The ball milling atmosphere was argon, the ball milling speed was fixed at 300r / min, and the ball milling time was 20h. Subsequently, 2% of epoxy resin was weighed and dissolved in an acetone solution, mixed and stirred for 30min, and the above powders were added into the solution, mixed and stirred evenly until completely evaporated; then transferred into a ring mold, compacted and molded under a pressure of 400MPa; finally, annealed at a temperature of 650℃ for 3h to obtain a nanocrystalline Fe-Ni soft magnetic composite material; Step (5) Mn 55 Bi 45 Preparation of Fe-Ni nanocomposite permanent magnetic materials The Mn prepared in step (3) was added to an inert gas glove box chamber with an oxygen content controlled at 8 ppm. 55 Bi 45 The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (4), and then placed in a high-energy ball mill equipped with steel balls. The ball mill cover is then tightened and taken out from the inert gas glove box. At this time, the ball mill contains a certain amount of Ar gas, which can protect the powder material from oxidation during the subsequent grinding process. The tightened ball mill is taken out from the inert gas glove box and fixed in a high-energy ball mill. Ball milling is performed according to the experimental conditions. After the ball milling is completed, the powder is collected in the inert gas glove box. After collecting the ball milled powder, about 0.4 g of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming. When the vacuum degree is lower than 2×10 -4 Pa, the tube sealing work is completed; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to complete the Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

[0021] Example 2

[0022] Step (1) Preparation of solid epoxy resin Add E51 resin and E20 resin into a four-necked flask, then raise the temperature to 70°C, adjust the stirring rate to 300r / min, and under this condition, add the chain extender polyaspartic acid ester resin dropwise, the dropping ratio is 6:1, the dropping time is controlled at 2h, and then keep the temperature for reaction for 2h, thereby obtaining the chain-extended epoxy resin, then add 1,4-cyclohexanedimethanol diglycidyl ether, and then add a mixed solvent (xylene: n-butanol = 3:1), adjust the solid content to 85%, and obtain a solid epoxy resin; Step (2) Preparation of MnBi alloy ingot The high-purity manganese metal raw materials and bismuth metal raw materials were ground and then crushed to a suitable size. The raw materials were weighed according to the nominal composition of Mn:Bi=55:45, and the raw materials were placed in the copper crucible of the arc melting furnace. The cavity of the arc melting furnace was then evacuated to a vacuum degree of 3×10 -3 After the melting temperature reaches 0.05 Pa, argon gas is injected to -0.05 Pa to ensure that the melting environment is in an oxygen-free environment. Then the melting is repeated 6 times to obtain a block ingot with uniform composition. Step (3) Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets The MnBi alloy ingot obtained in the above step (2) was placed in a tubular vacuum annealing furnace for annealing at an annealing temperature of 563K for 24 hours. When taken out, it was cooled to room temperature with water. The ingot was taken out for oxide scale polishing, crushed and ground in a glove box to obtain coarse powder, and sieved with 100 mesh. The powder was placed in a ball mill with a ball-to-material ratio of 12.5:1, and 3% oleic acid as a surfactant and 60 mL ethanol as a solvent were added. The ingot was then placed in a ball mill and the ball milling time was set to 0.5 hours. After the ball milling was completed, the slurry was washed with anhydrous ethanol and then mixed with paraffin to prepare anisotropic Mn 55 Bi 45 alloy magnetic powder, add acetone to the epoxy resin obtained in step (1), add it to the magnetic powder after it is completely melted, and stir it with a stirrer. As the stirring proceeds, the acetone gradually evaporates, and the epoxy resin and the magnetic powder are evenly mixed together. The magnetic powder mixed with the epoxy resin is molded and then cured at 120°C for 2h to obtain Mn 55 Bi 45 Alloy hard magnetic phase bonded magnet; Step (4) Preparation of nanocrystalline Fe-Ni soft magnetic composite material Fe powder and Ni powder were weighed according to a metering ratio of 100:5, added into a stainless steel ball mill, and high-energy ball milling was performed using a planetary high-energy ball mill. During the process, 3% alcohol was added to prevent powder oxidation. The ball milling atmosphere was argon, the ball milling speed was fixed at 300r / min, and the ball milling time was 20h. Subsequently, 2% of epoxy resin was weighed and dissolved in an acetone solution, mixed and stirred for 30min, and the above powders were added into the solution, mixed and stirred evenly until completely evaporated; then transferred into a ring mold, compacted and molded at a pressure of 400MPa; finally, annealed at a temperature of 600℃ for 3h to obtain a nanocrystalline Fe-Ni soft magnetic composite material; Step (5) Mn 55 Bi 45 Preparation of Fe-Ni nanocomposite permanent magnetic materials The Mn prepared in step (3) was added to an inert gas glove box chamber with an oxygen content controlled at 8 ppm. 55Bi 45 The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (4), and then placed in a high-energy ball mill equipped with steel balls. The ball mill cover is then tightened and taken out from the inert gas glove box. At this time, the ball mill contains a certain amount of Ar gas, which can protect the powder material from oxidation during the subsequent grinding process. The tightened ball mill is taken out from the inert gas glove box and fixed in a high-energy ball mill. Ball milling is performed according to the experimental conditions. After the ball milling is completed, the powder is collected in the inert gas glove box. After collecting the ball milled powder, about 0.4 g of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming. When the vacuum degree is lower than 2×10 -4 Pa, the tube sealing work is completed; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to complete the Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

[0023] Example 3

[0024] Step (1) Preparation of solid epoxy resin Add E51 resin and E20 resin into a four-necked flask, then raise the temperature to 70°C, adjust the stirring rate to 300r / min, and under this condition, dropwise add chain extender polyaspartic acid ester resin at a dropping ratio of 7:1, and control the dropping time to 2h. Keep the temperature for reaction for 2h to obtain chain-extended epoxy resin, then add 1,4-cyclohexanedimethanol diglycidyl ether, and then add a mixed solvent (xylene: n-butanol = 3:1), adjust the solid content to 85%, and obtain solid epoxy resin; Step (2) Preparation of MnBi alloy ingot The high-purity manganese metal raw materials and bismuth metal raw materials were ground and then crushed to a suitable size. The raw materials were weighed according to the nominal composition of Mn:Bi=55:45, and the raw materials were placed in the copper crucible of the arc melting furnace. The cavity of the arc melting furnace was then evacuated to a vacuum degree of 3×10 -3 After the melting temperature reaches 0.05 Pa, argon gas is injected to -0.05 Pa to ensure that the melting environment is in an oxygen-free environment. Then the melting is repeated 6 times to obtain a block ingot with uniform composition. Step (3) Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets The MnBi alloy ingot obtained in the above step (2) was placed in a tubular vacuum annealing furnace for annealing at an annealing temperature of 563K for 24 hours. When taken out, it was cooled to room temperature with water. The ingot was taken out for oxide scale polishing, crushed and ground in a glove box to obtain coarse powder, and sieved with 100 mesh. The powder was placed in a ball mill with a ball-to-material ratio of 12.5:1, and 3% oleic acid as a surfactant and 60 mL ethanol as a solvent were added. The ingot was then placed in a ball mill and the ball milling time was set for 1 hour. After the ball milling was completed, the slurry was washed with anhydrous ethanol and then mixed with paraffin to prepare anisotropic Mn 55 Bi 45 alloy magnetic powder, add acetone to the epoxy resin obtained in step (1), add it to the magnetic powder after it is completely melted, and stir it with a stirrer. As the stirring proceeds, the acetone gradually evaporates, and the epoxy resin and the magnetic powder are evenly mixed together. The magnetic powder mixed with the epoxy resin is molded and then cured at 120°C for 2h to obtain Mn 55 Bi 45 Alloy hard magnetic phase bonded magnet; Step (4) Preparation of nanocrystalline Fe-Ni soft magnetic composite material Fe powder and Ni powder were weighed according to a metering ratio of 100:5, added into a stainless steel ball mill, and high-energy ball milling was performed using a planetary high-energy ball mill. During the process, 3% alcohol was added to prevent powder oxidation. The ball milling atmosphere was argon, the fixed ball milling speed was 300r / min, and the ball milling time was 20h. Subsequently, 2% of epoxy resin was weighed and dissolved in an acetone solution, mixed and stirred for 30min, and the above powders were added into the solution, mixed and stirred evenly until completely evaporated; then transferred into a ring mold, compacted and molded under a pressure of 400MPa; finally, annealed at a temperature of 625℃ for 3h to obtain a nanocrystalline Fe-Ni soft magnetic composite material; Step (5) Mn 55 Bi 45 Preparation of Fe-Ni nanocomposite permanent magnetic materials The Mn prepared in step (3) was added to an inert gas glove box chamber with an oxygen content controlled at 8 ppm. 55 Bi 45The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (4), and then placed in a high-energy ball mill equipped with steel balls. The ball mill cover is then tightened and taken out from the inert gas glove box. At this time, the ball mill contains a certain amount of Ar gas, which can protect the powder material from oxidation during the subsequent grinding process. The tightened ball mill is taken out from the inert gas glove box and fixed in a high-energy ball mill. Ball milling is performed according to the experimental conditions. After the ball milling is completed, the powder is collected in the inert gas glove box. After collecting the ball milled powder, about 0.4 g of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming. When the vacuum degree is lower than 2×10 -4 Pa, the tube sealing work is completed; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to complete the Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

[0025] Example 4

[0026] Step (1) Preparation of solid epoxy resin Add E51 resin and E20 resin into a four-necked flask, then raise the temperature to 70°C, adjust the stirring rate to 300r / min, and under this condition, dropwise add chain extender polyaspartic acid ester resin, the dropwise addition ratio is 8:1, the dropwise addition time is controlled at 2h, and then keep warm for 2h to react, thereby obtaining chain-extended epoxy resin, then add 1,4-cyclohexanedimethanol diglycidyl ether, and then add a mixed solvent (xylene: n-butanol = 3:1), adjust the solid content to 85%, and obtain solid epoxy resin; Step (2) Preparation of MnBi alloy ingot The high-purity manganese metal raw materials and bismuth metal raw materials were ground and then crushed to a suitable size. The raw materials were weighed according to the nominal composition of Mn:Bi=55:45, and the raw materials were placed in the copper crucible of the arc melting furnace. The cavity of the arc melting furnace was then evacuated to a vacuum degree of 3×10 -3 After the melting temperature reaches 0.05 Pa, argon gas is injected to -0.05 Pa to ensure that the melting environment is in an oxygen-free environment. Then the melting is repeated 6 times to obtain a block ingot with uniform composition. Step (3) Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets The MnBi alloy ingot obtained in the above step (2) was placed in a tubular vacuum annealing furnace for annealing at an annealing temperature of 563K for 24 hours. When taken out, it was cooled to room temperature with water. The ingot was taken out for oxide scale polishing, crushed and ground in a glove box to obtain coarse powder, and sieved with 100 mesh. The powder was placed in a ball mill with a ball-to-material ratio of 12.5:1, and 3% oleic acid as a surfactant and 60 mL ethanol as a solvent were added. The ingot was then placed in a ball mill and the ball milling time was set for 3 hours. After the ball milling was completed, the slurry was washed with anhydrous ethanol and then mixed with paraffin to prepare anisotropic Mn 55 Bi 45 alloy magnetic powder, add acetone to the epoxy resin obtained in step (1), add it to the magnetic powder after it is completely melted, and stir it with a stirrer. As the stirring proceeds, the acetone gradually evaporates, and the epoxy resin and the magnetic powder are evenly mixed together. The magnetic powder mixed with the epoxy resin is molded and then cured at 120°C for 2h to obtain Mn 55 Bi 45 Alloy hard magnetic phase bonded magnet; Step (4) Preparation of nanocrystalline Fe-Ni soft magnetic composite material Fe powder and Ni powder were weighed according to a metering ratio of 100:5, added into a stainless steel ball mill, and high-energy ball milling was performed using a planetary high-energy ball mill. During the process, 3% alcohol was added to prevent oxidation of the powder. The ball milling atmosphere was argon, the ball milling speed was fixed at 300r / min, and the ball milling time was 20h. Subsequently, 2% of epoxy resin was weighed and dissolved in an acetone solution, mixed and stirred for 30min, and the above powders were added into the solution, mixed and stirred evenly until completely evaporated; then transferred into a ring mold, compacted and molded at a pressure of 400MPa; finally, annealed at a temperature of 700℃ for 3h to obtain a nanocrystalline Fe-Ni soft magnetic composite material; Step (5) Mn 55 Bi 45 Preparation of Fe-Ni nanocomposite permanent magnetic materials The Mn prepared in step (3) was added to an inert gas glove box chamber with an oxygen content controlled at 8 ppm. 55 Bi 45The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (4), and then placed in a high-energy ball mill equipped with steel balls. The ball mill cover is then tightened and taken out from the inert gas glove box. At this time, the ball mill contains a certain amount of Ar gas, which can protect the powder material from oxidation during the subsequent grinding process. The tightened ball mill is taken out from the inert gas glove box and fixed in a high-energy ball mill. Ball milling is performed according to the experimental conditions. After the ball milling is completed, the powder is collected in the inert gas glove box. After collecting the ball milled powder, about 0.4 g of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming. When the vacuum degree is lower than 2×10 -4 Pa, the tube sealing work is completed; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to complete the Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

[0027] Comparative Example 1

[0028] Step (1) Preparation of solid epoxy resin Add E51 resin and E20 resin into a four-necked flask, then raise the temperature to 70°C, adjust the stirring rate to 300r / min, and under this condition, add chain extender polyaspartic acid ester resin dropwise, the dropping ratio is 9:1, the dropping time is controlled at 2h, and then keep the temperature for reaction for 2h, thereby obtaining chain-extended epoxy resin, then add 1,4-cyclohexanedimethanol diglycidyl ether, and then add a mixed solvent (xylene: n-butanol = 3:1), adjust the solid content to 85%, and obtain solid epoxy resin; Step (2) Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets The MnBi alloy ingot was placed in a tubular vacuum annealing furnace for annealing at a temperature of 563 K for 24 hours. When taken out, it was cooled to room temperature with water. The ingot was taken out for oxide skin polishing, crushed and ground in a glove box to obtain coarse powder, and sieved with 100 mesh. 2 powders were placed in a ball mill with a ball-to-material ratio of 12.5:1, and 3% oleic acid by weight of the powder was added as a surfactant, 60 mL of ethanol was used as a solvent, and then placed in a ball mill for 4 hours. After the ball milling was completed, the slurry was washed with anhydrous ethanol and then mixed with paraffin to prepare anisotropic Mn 55 Bi 45 alloy magnetic powder, add acetone to the epoxy resin obtained in step (1), add it to the magnetic powder after it is completely melted, and stir it with a stirrer. As the stirring proceeds, the acetone gradually evaporates, and the epoxy resin and the magnetic powder are evenly mixed together. The magnetic powder mixed with the epoxy resin is molded and then cured at 120°C for 2h to obtain Mn55 Bi 45 Alloy hard magnetic phase bonded magnet; Step (3) Preparation of nanocrystalline Fe-Ni soft magnetic composite material Fe powder and Ni powder were weighed according to a metering ratio of 100:5, added into a stainless steel ball mill, and high-energy ball milling was performed using a planetary high-energy ball mill. During the process, 3% alcohol was added to prevent powder oxidation. The ball milling atmosphere was argon, the fixed ball milling speed was 300r / min, and the ball milling time was 20h. Subsequently, 2% of epoxy resin was weighed and dissolved in an acetone solution, mixed and stirred for 30min, and the above powders were added into the solution, mixed and stirred evenly until completely evaporated; then transferred into a ring mold, compacted and molded under a pressure of 400MPa; finally, annealed at a temperature of 575℃ for 3h to obtain a nanocrystalline Fe-Ni soft magnetic composite material; Step (4) Mn 55 Bi 45 Preparation of Fe-Ni nanocomposite permanent magnetic materials The Mn prepared in step (2) was added to an inert gas glove box chamber with an oxygen content controlled at 8 ppm. 55 Bi 45 The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (3), and then placed in a high-energy ball mill equipped with steel balls. The ball mill cover is then tightened and taken out from the inert gas glove box. At this time, the ball mill contains a certain amount of Ar gas, which can protect the powder material from oxidation during the subsequent grinding process. The tightened ball mill is taken out from the inert gas glove box and fixed in a high-energy ball mill. Ball milling is performed according to the experimental conditions. After the ball milling is completed, the powder is collected in the inert gas glove box. After collecting the ball milled powder, about 0.4 g of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming. When the vacuum degree is lower than 2×10 -4 Pa, the tube sealing work is completed; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to complete the Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

[0029] Comparative Example 2

[0030] Step (1) Preparation of solid epoxy resin Add E51 resin and E20 resin into a four-necked flask, then raise the temperature to 70°C, adjust the stirring rate to 300r / min, and under this condition, dropwise add chain extender polyaspartic acid ester resin at a ratio of 10:1, and control the dropping time to 2h. Keep the temperature for reaction for 2h to obtain chain-extended epoxy resin, then add 1,4-cyclohexanedimethanol diglycidyl ether, and then add a mixed solvent (xylene: n-butanol = 3:1), adjust the solid content to 85%, and obtain solid epoxy resin; Step (2) Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets The MnBi alloy ingot was placed in a tubular vacuum annealing furnace for annealing at a temperature of 563 K for 24 hours. When taken out, it was cooled to room temperature with water. The ingot was taken out for scale polishing, crushed and ground in a glove box to obtain coarse powder, and sieved with 100 mesh. 2 powders were placed in a ball mill with a ball-to-material ratio of 12.5:1, and 3% oleic acid by weight of the powder was added as a surfactant, 60 mL of ethanol was used as a solvent, and then placed in a ball mill for 5 hours. After the ball milling was completed, the slurry was washed with anhydrous ethanol and then mixed with paraffin to prepare anisotropic Mn 55 Bi 45 alloy magnetic powder, add acetone to the epoxy resin obtained in step (1), add it to the magnetic powder after it is completely melted, and stir it with a stirrer. As the stirring proceeds, the acetone gradually evaporates, and the epoxy resin and the magnetic powder are evenly mixed together. The magnetic powder mixed with the epoxy resin is molded and then cured at 120°C for 2h to obtain Mn 55 Bi 45 Alloy hard magnetic phase bonded magnet; Step (3) Preparation of nanocrystalline Fe-Ni soft magnetic composite material Fe powder and Ni powder were weighed according to a metering ratio of 100:5, added into a stainless steel ball mill, and high-energy ball milling was performed using a planetary high-energy ball mill. During the process, 3% alcohol was added to prevent oxidation of the powder. The ball milling atmosphere was argon, the ball milling speed was fixed at 300r / min, and the ball milling time was 20h. Subsequently, 2% of epoxy resin was weighed and dissolved in an acetone solution, mixed and stirred for 30min, and the above powders were added into the solution, mixed and stirred evenly until completely evaporated; then transferred into a ring mold, compacted and molded at a pressure of 400MPa; finally, annealed at a temperature of 550℃ for 3h to obtain a nanocrystalline Fe-Ni soft magnetic composite material; Step (4) Mn 55 Bi 45 Preparation of Fe-Ni nanocomposite permanent magnetic materials The Mn prepared in step (2) was added to an inert gas glove box chamber with an oxygen content controlled at 7 ppm.55 Bi 45 The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (3), and then placed in a high-energy ball mill equipped with steel balls. The ball mill cover is then tightened and taken out from the inert gas glove box. At this time, the ball mill contains a certain amount of Ar gas, which can protect the powder material from oxidation during the subsequent grinding process. The tightened ball mill is taken out from the inert gas glove box and fixed in a high-energy ball mill. Ball milling is performed according to the experimental conditions. After the ball milling is completed, the powder is collected in the inert gas glove box. After collecting the ball milled powder, about 0.4 g of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming. When the vacuum degree is lower than 2×10 -4 Pa, the tube sealing work is completed; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to complete the Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

[0031] Comparison of detection experiments: The nanocomposite permanent magnetic materials obtained in Examples 1 to 4 and Comparative Example Products 1 and 2 were tested. The specific testing method is as follows: Viscosity testing Detection of viscosity of epoxy resin system: Use digital viscometer to detect the viscosity of different epoxy resins. Set the temperature at 25°C, select the rotor within the measurement range, adjust the digital viscometer to keep it horizontal, set various data, and test the viscosity of each epoxy resin sample 3 times, and take the average value of the 3 times.

[0032] Magnetic properties analysis After annealing, Mn 55 Bi 45 The alloy ingot was crushed, ground and sieved, and then subjected to high-energy ball milling for 0.5 hours, 1 hour, 2 hours, 4 hours, 5 hours and 6 hours to prepare Mn 55 Bi 45 Alloy, this patent uses a soft magnetic AC test device to test Mn 55 Bi 45 The magnetic properties of the Fe-Ni nanocomposite permanent magnet material were analyzed and tested, and the saturation magnetization intensity and coercive force of the samples were analyzed separately. The results are shown in the following table.

[0033] Table 1 Viscosity test

[0034] As can be seen from Table 1, the viscosity performance of Example 1 is the best, while that of Comparative Example 2 is relatively poor. In Example 1, the viscosity of the epoxy resin reaches 42000 mPa·s, while in Comparative Example 2 it is only 24000 mPa·s. It can be seen that the viscosity of the epoxy resin decreases as the mass of the raw material E51 resin increases. The more the mass of the raw material E51 resin, the lower the viscosity of the epoxy resin. The higher the viscosity, the better the toughness of the epoxy resin. The improvement of toughness plays an important role in the subsequent composite of magnetic materials and provides an excellent performance foundation for the subsequent composite.

[0035] Table 2 Coercivity test

[0036] As shown in Table 2, Example 1 has the best performance. The intrinsic coercivity reaches 13.4Oe, which is the highest. Comparative Example 2 is relatively poor, with an intrinsic coercivity of 5.1. This shows that the intrinsic coercivity increases with the extension of ball milling time. However, when the ball milling time is 2h, the intrinsic coercivity reaches its peak, and then decreases with the extension of ball milling time. Therefore, in the present invention, the ball milling time is most suitable for 2h, so that Mn 55 Bi 45 Alloy hard magnetic phase bonded magnets have the best intrinsic coercivity.

[0037] Table 3 Magnetic properties test

[0038] As shown in Table 3, Example 1 has the best performance, while Comparative Example 2 is relatively poor. The saturation magnetization intensity of Example 1 is as high as 33.1Am 2 / kg, comparative example 2 only 20.1Am 2 / kg, it can be seen that the saturation magnetization increases with the increase of annealing temperature. When the annealing temperature reaches 650℃, the saturation magnetization reaches its peak, and then it weakens with the increase of annealing temperature. In summary, when the annealing temperature of nanocrystalline Fe-Ni soft magnetic composite material is 650℃, its saturation magnetization is optimal and its magnetic properties are the best.

[0039] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A method for preparing a nanocomposite permanent magnetic material having high magnetic energy product and strong coercivity, characterized in that: include: Step (1) preparation of solid epoxy resin, step (2) preparation of MnBi alloy ingot, step (3) preparation of Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets, step (4) Preparation of nanocrystalline Fe-Ni soft magnetic composite materials, step (5) Mn 55 Bi 45 / Preparation of Fe-Ni nanocomposite permanent magnetic materials; Wherein, the preparation of the nanocrystalline Fe-Ni soft magnetic composite material in step (4) comprises: Fe powder and Ni powder are weighed according to a certain stoichiometric ratio, and high-energy ball milling is performed, during which alcohol is added to prevent oxidation of the powders, and the ball milling atmosphere is argon. Subsequently, epoxy resin is weighed and dissolved in an acetone solution, mixed and stirred, and the above powders are added to the solution, mixed and stirred evenly until completely evaporated; then compacted and formed under a certain pressure; finally, annealed at a high temperature for a period of time to obtain a nanocrystalline Fe-Ni soft magnetic composite material; Step (5) Mn 55 Bi 45 / The preparation of Fe-Ni nanocomposite permanent magnetic materials includes: The Mn obtained in step (3) 55 Bi 45 The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (4), and then ball milling is performed. After the ball milling is completed, the powder is collected; after the ball milling powder is collected, a certain amount of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming. When the vacuum degree is lower than a certain amount, the tube sealing work is completed; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to complete the process, and finally Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

2. The preparation of nanocomposite permanent magnetic material with high magnetic energy product and strong coercivity according to claim 1, characterized in that: Step (1) Preparation of solid epoxy resin Add E51 resin and E20 resin into a four-necked flask, then raise the temperature, adjust the stirring rate, and under this condition, dropwise add the chain extender polyaspartic acid ester resin, control the dropping time, and then carry out heat preservation reaction to obtain the chain-extended epoxy resin, then add 1,4-cyclohexanedimethanol diglycidyl ether, and then add a mixed solvent (xylene: n-butanol), adjust the solid content, and obtain a solid epoxy resin; Step (2) Preparation of MnBi alloy ingot The high-purity manganese metal raw material and bismuth metal raw material are ground and then crushed to a suitable size, and a certain amount of raw materials are weighed respectively, and the raw materials are placed in a copper crucible of an arc melting furnace, and then the cavity of the arc melting furnace is evacuated and filled with argon gas to ensure that the melting environment is in an oxygen-free environment, and then the melting is repeated to obtain a block ingot with uniform composition; Step (3) Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets The MnBi alloy ingot obtained in the above step (2) is placed in a tubular vacuum annealing furnace for annealing, and a certain annealing temperature and time are set. When taken out, it is water-cooled to room temperature, and the ingot is taken out for oxide scale grinding, crushed and ground in a glove box to obtain coarse powder, sieved, and the powder is placed in a ball mill, and the ball-to-material ratio is set, and oleic acid is added as a surfactant and ethanol is used as a solvent. Then, the powder is placed in a ball mill and a certain ball milling time is set. After the ball milling is completed, the slurry is washed with anhydrous ethanol and then mixed with paraffin to prepare anisotropic Mn 55 Bi 45 Mn alloy magnetic powder, add acetone to the epoxy resin obtained in step (1), add it to the magnetic powder after it is completely melted, and stir it with a stirrer. As the stirring proceeds, the acetone gradually evaporates, and the epoxy resin and the magnetic powder are evenly mixed together. The magnetic powder mixed with the epoxy resin is molded and then cured at a certain temperature to obtain Mn alloy magnetic powder. 55 Bi 45 Alloy hard magnetic phase bonded magnet; Step (4) Preparation of nanocrystalline Fe-Ni soft magnetic composite material Fe powder and Ni powder are weighed according to a certain metering ratio, added into a stainless steel ball mill, and high-energy ball milling is performed using a planetary high-energy ball mill. During the process, alcohol is added to prevent oxidation of the powder. The ball milling atmosphere is argon gas. The ball milling speed is fixed and the ball milling time is set. Subsequently, epoxy resin is weighed and dissolved in an acetone solution, mixed and stirred for a certain period of time, and the above powders are added into the solution, mixed and stirred evenly until completely evaporated; then the powders are transferred into a ring mold and compacted under a certain pressure; finally, the nanocrystalline Fe-Ni soft magnetic composite material is obtained by annealing at high temperature for a period of time. Step (5) Mn 55 Bi 45 Preparation of Fe-Ni nanocomposite permanent magnetic materials The Mn prepared in step (3) was added to the inert gas glove box chamber with a certain oxygen content. 55 Bi 45 The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (4), and then placed in a high-energy ball mill equipped with steel balls, and then the ball mill cover is tightened and taken out from the inert gas glove box. At this time, the ball mill already contains a certain amount of Ar gas, which can protect the powder material from oxidation during the subsequent grinding process; the tightened ball mill is taken out from the inert gas glove box and fixed in a high-energy ball mill, and ball milling is performed according to the experimental set conditions. After the ball milling is completed, the powder is collected in the inert gas glove box; after collecting the ball milled powder, a certain amount of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming, and the tube sealing work is completed when the vacuum degree is lower than a certain amount; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to obtain Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

3. The preparation of nanocomposite permanent magnetic material with high magnetic energy product and strong coercivity according to claim 2, characterized in that: Step (1) Preparation of solid epoxy resin Add E51 resin and E20 resin into a four-necked flask, then raise the temperature to 70-80°C, then adjust the stirring rate to 300-400r / min, and under this condition, add the chain extender polyaspartic acid ester resin dropwise, the addition ratio is 4:1-12:3, the addition time is controlled between 2-3h, and then keep the temperature for 2-3h to obtain the chain-extended epoxy resin, then add 1,4-cyclohexanedimethanol diglycidyl ether, and then add a mixed solvent (xylene: n-butanol = 3:1-5:2), adjust the solid content to 85-90%, and obtain a solid epoxy resin.

4. The preparation of nanocomposite permanent magnetic material with high magnetic energy product and strong coercivity according to claim 3, characterized in that: Step (2) Preparation of MnBi alloy ingot The high-purity manganese metal raw materials and bismuth metal raw materials were ground and then crushed to a suitable size. The raw materials were weighed according to the nominal composition of Mn:Bi=55:45-60:50, and the raw materials were placed in the copper crucible of the arc melting furnace. The cavity of the arc melting furnace was evacuated to a vacuum degree of (3-3.5)×10 -3 Pa, then argon is injected to - (0.05-0.07) Pa to ensure that the melting environment is in an oxygen-free environment, and then the melting is repeated 6-7 times to obtain a block ingot with uniform composition.

5. The preparation of nanocomposite permanent magnetic material with high magnetic energy product and strong coercivity according to claim 4, characterized in that: Step (3) Mn 55 Bi 45 Preparation of alloy hard magnetic phase bonded magnets The MnBi alloy ingot obtained in the above step (2) is placed in a tubular vacuum annealing furnace for annealing at an annealing temperature of 563-570K for an annealing time of 24-26 hours. When taken out, the ingot is cooled to room temperature with water. The ingot is taken out for oxide scale polishing, crushed and ground in a glove box to obtain a coarse powder, and sieved with 100-150 mesh. 2-4g of the powder is placed in a ball mill with a ball-to-material ratio of 12.5:1-25:2, and 3-3.5% of oleic acid by weight of the powder is added as a surfactant, 60-80mL of ethanol is used as a solvent, and then the ingot is placed in a ball mill for a ball milling time of 0.5-6 hours. After the ball milling is completed, the slurry is washed with anhydrous ethanol and then mixed with paraffin to prepare anisotropic Mn 55 Bi 45 alloy magnetic powder, add acetone to the epoxy resin obtained in step (1), add it to the magnetic powder after it is completely melted, and stir it with a stirrer. As the stirring proceeds, the acetone gradually evaporates, and the epoxy resin and the magnetic powder are evenly mixed together. The magnetic powder mixed with the epoxy resin is molded and then cured at 120-140°C for 2-3h to obtain Mn 55 Bi 45 Alloy hard magnetic phase bonded magnet.

6. The preparation of nanocomposite permanent magnetic material with high magnetic energy product and strong coercivity according to claim 5, characterized in that: Step (4) Preparation of nanocrystalline Fe-Ni soft magnetic composite material Fe powder and Ni powder are weighed according to a metering ratio of 100:5-200:10, added into a stainless steel ball mill, and high-energy ball milling is performed using a planetary high-energy ball mill. During the process, 3-4% alcohol is added to prevent powder oxidation. The ball milling atmosphere is argon, the fixed ball milling speed is 300-350r / min, and the ball milling time is 20-50h. Subsequently, 2-3% of epoxy resin with a mass fraction is weighed and dissolved in an acetone solution, mixed and stirred for 30-45min, and the above powders are added into the solution, mixed and stirred evenly until completely evaporated; then transferred to a ring mold, compacted and molded at a pressure of 400-450MPa; finally, annealed at a temperature of 550-700℃ for 3-4h to obtain a nanocrystalline Fe-Ni soft magnetic composite material.

7. The preparation of nanocomposite permanent magnetic material with high magnetic energy product and strong coercivity according to claim 6, characterized in that: Step (5) Mn 55 Bi 45 Preparation of Fe-Ni nanocomposite permanent magnetic materials The Mn prepared in step (3) was added to an inert gas glove box chamber with an oxygen content controlled at 6-8 ppm. 55 Bi 45 The alloy hard magnetic phase bonded magnet is uniformly mixed with the nanocrystalline Fe-Ni soft magnetic composite material obtained in step (4), and then placed in a high-energy ball mill equipped with steel balls. The ball mill cover is then tightened and taken out from the inert gas glove box. At this time, the ball mill contains Ar gas, which can protect the powder material from oxidation during the subsequent grinding process. The tightened ball mill is taken out from the inert gas glove box and fixed in a high-energy ball mill. Ball milling is performed according to the conditions. After the ball milling is completed, the powder is collected in the inert gas glove box. After collecting the ball milled powder, about 0.4-0.5g of the ball milled powder is placed in a quartz glass tube, which is installed on a tube sealing machine for vacuuming. When the vacuum degree is lower than (2-3)×10 -4 Pa, the tube sealing work is completed; finally, the vacuum-sealed quartz glass tube is placed in a box-type resistance furnace to complete the Mn 55 Bi 45 / Fe-Ni nanocomposite permanent magnetic materials.

Citation Information

Patent Citations

  • Method for preparing high-coercivity manganese-bismuth magnetic powder with modified organic light rare-earth complex

    CN108346499A

  • Magnet composition and bonded magnet using the same

    JP2001217109A

  • Ferromagnetic nanoparticles with high magnetocrystalline anisotropy for MICR toner applications

    US20090325098A1

  • Process for preparing scalable quantities of high purity manganese bismuth magnetic materials for fabrication of permanent magnets

    US20150110664A1

  • HIGH PERFORMANCE PERMANENT MAGNET BASED ON MnBi AND METHOD TO MANUFACTURE SUCH A MAGNET

    US20150325349A1